2016
DOI: 10.1590/s0102-865020160120000010
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of obesity in rodents. An integrative review

Abstract: PURPOSE:To perform an integrative review of the main animal disease models in rodents used for obesity. METHODS:Research was conducted in the CAPES Portal database using the following keywords "obesity animal models, diet and rodents", published between the years 2010 to 2016. We found 108 articles, of which 19 were selected and analyzed in full for this study. RESULTS:Larger part of publications occurred in the last 6 years, the rats (n = 10) were used in the same proportion mice (n = 10).The choice of male a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 27 publications
1
25
0
1
Order By: Relevance
“…In the present study, the LGD was high in fat and cholesterol, and it was fed to mice for 10 weeks. In these conditions, the LGD can induce weight gain and obesity, as previously observed [ 24 , 26 , 34 ], while pioglitazone administration improved body weight, adipose mass, serum cholesterol, and serum triglyceride. Decreased LDL and increased HDL levels were also detected in pioglitazone-treated mice, respectively ( Table 1 ).…”
Section: Discussionsupporting
confidence: 64%
“…In the present study, the LGD was high in fat and cholesterol, and it was fed to mice for 10 weeks. In these conditions, the LGD can induce weight gain and obesity, as previously observed [ 24 , 26 , 34 ], while pioglitazone administration improved body weight, adipose mass, serum cholesterol, and serum triglyceride. Decreased LDL and increased HDL levels were also detected in pioglitazone-treated mice, respectively ( Table 1 ).…”
Section: Discussionsupporting
confidence: 64%
“…These constellations of symptoms mimic major parameters of MetS. In the literature, HF mice have been widely used to model MetS or its individual parameters such as obesity [ 56 ], prediabetes [ 38 ], hyperlipidemia [ 57 ] or MetS [ 58 ]. In the current study, HF mice did not have significant hypertriglyceridemia within the duration of our experiment at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…Rodents which have the ability to develop obesity through genetic changes, such as leptin signaling defects (ob / ob mouse) or an autosomal recessive mutation in the fatty ( fa ) gene on chromosome 5 ( Zucker - fa / fa –fatty rat) have mainly been used [ 8 ]. In addition, hypercaloric diets are most frequently used to generate obese rodent models because they resemble the genesis of obesity in humans [ 9 ]. Cao et al (2012) [ 10 ] have demonstrated that high-fat diets vary between 30–60% of calories coming from saturated fat, such as lard, beef tallow or coconut oil, while the sugar content, for which sucrose and fructose are generally used [ 11 , 12 ] typically comprises 60–65%.…”
Section: Introductionmentioning
confidence: 99%